Shallow-water species of Beania Johnston, 1840 (Bryozoa, Cheilostomata) from the tropical and subtropical Western Atlantic - Vieira, Leandro M.; Migotto, Alvaro E.; Winston, Judith E. (Zootaxa, 2010)
This paper describes four new species of the bryozoan genus Beania from the Brazilian coast. Two of them have been previously recorded in the western Atlantic as Beania hirtissima (Heller, 1867) and Beania mirabilis Johnston, 1840, respectively; they are redescribed here as Beania americana n. sp. and Beania mirabilissima n. sp. Two reticulate species, Beania correiae n. sp. and Beania metrii n. sp., are newly described. Descriptions of four other species of Beania from the region are also included: Beania australis Busk, 1852, Beania cupulariensis Osburn, 1914, Beania klugei Cook, 1968 and Beania maxilladentata Ramalho, Muricy & Taylor, 2010.